PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN SEBAGAI ALAT PENILAIAN KINERJA PUSAT BIAYA (Studi Kasus Pada PT PLN (Persero) Unit Pelaksana Pengendalian Pembangkitan Mahakam Periode Tahun 2018) - Indah Tri Utami Agustini; Zulfikar Zulfikar; Novia Dwiariyani (Jurnal Eksis, 2019)
This study aims to determine the appropriateness of the application of responsibility accounting as a cost center performance appraisal tool with the conditions for its application, the characteristics of responsibility accounting, and the stages of performance evaluation according to Mulyadi at PT PLN (Persero) UPDK Mahakam. Data were taken through interviews and literature study. The data analysis technique used in this study was a qualitative comparative descriptive analysis. The results of this study indicate that the application of responsibility accounting as a means of assessing the navel cost performance at PT PLN (Persero) UPDK Mahakam is sufficient in accordance with the requirements for implementation, the characteristics of responsibility accounting, and the stage of performance evaluation according to Mulyadi. This can be seen from the results of calculating the percentage of compliance with the established indicators which is equal to 75%. Indicators that are not yet suitable are account codes that have not carried out controlled and uncontrolled cost segregation in their accountability reports, so they cannot display the limits of the manager's responsibilities. Keywords: responsibility accounting, performance, cost center